Perlakuan Aset Biologis Berdasarkan PSAK 69 Pada Peternakan Itik Petelur - Kholifatul Khoiroh; Dyah Pravitasari (Universitas Islam Nahdlatul Ulama Jepara, 2023)
The background to this research is that the treatment of biological assets in Pak Susanto's egg-laying duck farm in Dono village, Sendang District, Tulungagung Regency is not accurate. The research aims to analyze the treatment of biological assets on the farm through the application of the Statement of Financial Accounting Standards (SFAS) 69 regarding agriculture, then compare it with before the implementation of SFAS 69. This research was qualitative descriptive research where data was obtained by observation, in-depth interviews, documentation, and triangulation. Data analysis in this research referred to the theory of Miles and Huberman including data reduction, data display, and data conclusion. The research results showed that livestock owners had not applied SFAS 69 to the biological assets being treated. Therefore, there was a difference between before and after the implementation of SFAS 69. The value of the ducks on the duck farm was estimated at IDR 27,000,000 by the owner. After re-measuring the value of biological assets, there was a difference of IDR 17,771,800, with the total yield of biological assets being IDR 44,771,800. The farm owner also had not recorded proper financial reports